1989
DOI: 10.1111/j.1349-7006.1989.tb01670.x
|View full text |Cite
|
Sign up to set email alerts
|

Promotion by Nialamide of Gastric Carcinogenesis Induced by N‐Methyl‐N′‐nitro‐N‐nitrosoguanidine in Wistar Rats

Abstract: The effects of nialamide, a monoamine oxidase inhibitor, on the incidence, number, and histology of gastric cancers induced by N‐methyl‐N′‐nitro‐N‐nitrosoguanidine (MNNG) were investigated in male Wistar rats. Rats were given subcutaneously 50 mg/kg body weight of nialamide in depot form every other day after 25 weeks of oral treatment with MNNG. Prolonged alternate‐day administration of nialamide caused a significant increase in the incidence and number of gastric cancers of the glandular stomach in week 52, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 17 publications
0
36
1
Order By: Relevance
“…9 I now describe in greater detail the aforementioned 7 lines of evidence that support an etiological role for NE in some types of cancer. The first line of evidence has been put forth primarily by a group of researchers in Japan during the last several decades, [11][12][13][14][15][16][17][18][19][20] as well as by some Russian scientists [21][22][23] and others. 24,25 This line indicates that in rodents the level of NE, or degree of activation of adrenoceptors with drugs, in certain bodily tissues correlates with the degree of tumorigenesis in those tissues.…”
Section: Literature Search Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 I now describe in greater detail the aforementioned 7 lines of evidence that support an etiological role for NE in some types of cancer. The first line of evidence has been put forth primarily by a group of researchers in Japan during the last several decades, [11][12][13][14][15][16][17][18][19][20] as well as by some Russian scientists [21][22][23] and others. 24,25 This line indicates that in rodents the level of NE, or degree of activation of adrenoceptors with drugs, in certain bodily tissues correlates with the degree of tumorigenesis in those tissues.…”
Section: Literature Search Detailsmentioning
confidence: 99%
“…24,25 This line indicates that in rodents the level of NE, or degree of activation of adrenoceptors with drugs, in certain bodily tissues correlates with the degree of tumorigenesis in those tissues. In particular, during chemically induced carcinogenesis, when the level of NE is increased with drugs such as bombesin 11,12 or the tricyclic antidepressant desipramine, 13 or a low protein diet, 14,15 tumorigenesis increases; when the level of NE is decreased with 6-hydroxydopamine, 16 phenylalanine, 17 or cysteamine, 18,19 tumorigenesis decreases. However, when the level of NE is decreased with clonidine, tumorigenesis is unaffected.…”
Section: Literature Search Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, we found that long-term administration of bombesin after MNNG treatment significantly increased the incidence of gastric cancers induced by MNNG [8]. However, in a gastric cancer model, peritoneal metastasis from the gastric cancers was observed in only one (7%) of 15 tumor-bearing rats (data not shown).…”
Section: Discussionmentioning
confidence: 96%
“…Bombesin has important roles in the physiology and pathology of the gastrointestinal system [5][6][7]. Previously, we [8] found that bombesin enhanced gastric carcinogenesis in Wistar rats after the administration of N-methyl-NЈ-nitro-N-nitrosoguanidine (MNNG) was stopped. These findings suggested that bombesin might induce the development of peritoneal metastasis from gastric cancers.…”
Section: Introductionmentioning
confidence: 99%